Advanced catalytic ozonation for degradation of pharmaceutical pollutants―A review. (February 2022) - Issaka, Eliasu; AMU-Darko, Jesse Nii-Okai; Yakubu, Salome; Fapohunda, Funmilayo Omotoyosi; Ali, Nisar; Bilal, Muhammad
Abstract: Various chemical treatment techniques are involved in removing refractory organic compounds from water and wastewater using the oxidation reaction of hydroxyl radicals ( OH). The use of catalysts in advanced catalytic ozonation is likely to improve the decomposition of molecular ozone to generate highly active free radicals that facilitate the rapid and efficient mineralization and degradation of numerous organics. For the degradation of toxic organic pollutants in wastewater, the advanced catalytic ozonation process has been widely applied in recent years. Low utilization efficiency of ozone and ineffective mineralization of organic contaminants by ozone can be remedied with advanced catalytic ozonation. Advanced catalytic ozonation has gained popularity because of these merits. However, homogeneous catalytic ozonation has the disadvantage of producing secondary contaminants from the addition of metallic ions. Heterogeneous catalytic ozonation can overcome this drawback by utilizing metals, metallic oxides, and carbon materials as a catalyst of efficacy and stability. This review discusses various aspects of catalytic ozonation in wastewater treatment of pharmaceutical pollutants, application of catalytic ozonation process in typical wastewater, and prospects in advancing the techniques in heterogeneous catalytic ozonation. Graphical abstract: Image 1 Highlights: Refractory organic contaminants in water threaten environmental safety and human health. Treatment efficiency of advanced catalytic ozonation for pharmaceutical pollutants is summarized. Heterogeneous catalytic ozonation is promising technology for treating organic wastewater. Current challenges, problems and prospective research directions are outlined.